8th International Congress on Energy Fluxes and Radiation Effects 2022
DOI: 10.56761/efre2022.r1-p-013501
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in the material of the absorbed energy of a space-limited beam flow of high-energy electrons

Abstract: This article describes the numerical simulation of the energy loss of a high-energy electron flow in matter using the Casino program. The simulation results are confirmed experimentally. Materials MgF2, YAG, MgAl2O4, BaMgF4 were chosen for calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…We found that the synthesis is realized in less than 1 s and without the addition of any substances to facilitate the synthesis and only due to the energy of the radiation flux. It was found in [57] that the result of the synthesis depends on the degree of purity, the particle size of the starting material, the flux power density, and the electron energy. Synthesis does not require particles of initial nanosized powders; they will disappear during synthesis due to charging.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the synthesis is realized in less than 1 s and without the addition of any substances to facilitate the synthesis and only due to the energy of the radiation flux. It was found in [57] that the result of the synthesis depends on the degree of purity, the particle size of the starting material, the flux power density, and the electron energy. Synthesis does not require particles of initial nanosized powders; they will disappear during synthesis due to charging.…”
Section: Discussionmentioning
confidence: 99%